Late Recurrence of Mucinous Adenocarcinoma after Lung Transplantation: A Case Report and Literature Review - Eveline Claeys; Nico De Crem; Pierre Van Mol; Arno Vanstapel; Laurens Joseph Ceulemans; Dirk Van Raemdonck; Christophe Dooms; Walter De Wever; Christophe Michel Deroose; Isabelle Vanden Bempt; Birgit Weynand; Robin Vos; et al. (Case Reports in Oncology)
Introduction: Invasive mucinous adenocarcinoma (IMA) of the lung has a less aggressive behavior than other adenocarcinoma subtypes. Overall, the propensity for nodal and distant metastases is low, but spread throughout the lungs is frequent. The radiographic “ground glass” presentation makes differentiation between infectious and inflammatory consolidations challenging, and the diagnosis of malignancy is often unexpected. Case Presentation: A 50-year-old patient underwent double lung transplantation (LTx) in July 2018 for progressive fibrosing interstitial lung disease (ILD). IMA was unexpectedly found in the explant lungs. Pre-transplant PET-CT scans suggested inflammatory ILD without malignancy. Endobronchial ultrasound-guided transbronchial fine needle aspiration of the enlarged mediastinal lymph nodes demonstrated no evidence of malignancy. Post-transplant pathology confirmed stage IVA IMA with a KRAS G12D mutation. After 3 years, recurrent IMA was detected. The asymptomatic patient remains under close surveillance with stable lung function, and tailored treatment will be considered if progression occurs. Conclusion: IMA is currently rarely considered an indication for LTx. The risk of recurrence after transplantation is substantial, and recurrence negatively impacts long-term post-transplant prognosis. Incidental adenocarcinoma in explant lungs will remain a complication of imperfect transplant recipient selection. A high index of suspicion of disease recurrence in the donor lungs should be maintained in these patients. Further research is required to understand the optimal screening, treatment, and follow-up of these patients.